Attention deficit hyperactivity disorder and anti-Purkinje autoantibodies: no link?. Issue 4 (2nd October 2019) - Cetin, Fatih Hilmi; Cetin, Feyza; Isik, Yasemen; Guney, Esra; Alp, Feyza; Aksoy, Altan
ABSTRACT: OBJECTIVES: Attention Deficit Hyperactivity Disorder (ADHD) is a neurobehavioral disorder that begins in early childhood, and many factors play role in its etiology. Many studies have been conducted to identify the causes of ADHD, but the exact factors are still unknown. Although cerebellar dysfunction in the etiology of ADHD was shown in different studies, the possible causes of dysfunction and the role of neuroinflammation among these causes has not been clarified yet. Anti-Yo is an antibody against the antigens in the cytoplasm of purkinje cells and indicates cerebellar degeneration, and Anti-Hu and Anti-Ri are antibodies against cellular nuclear antigens of purkinje cells. This study aimed to evaluate the role of neuroinflammation that is a potential cause of cerebellar dysfunction, which is thought to be an important factor in the development of ADHD. METHODS: This is a cross-sectional and descriptive study that aimed to evaluate the potential association between ADHD and cerebellar neuroinflammation by comparing the serum anti-purkinje cell antibody measurements between case and control groups. The cases were recruited at the Gazi University Child Psychiatry Department, and laboratory analyses were performed at the Ankara Numune Research and Training Hospital Medical Microbiology Department. Sixty children and adolescents with ADHD, and 60 healthy controls were planned to be included in the study. Cases that admitted with ADHD symptoms were given Conners teacher forms according to routine procedure; then the cases with scores over the cut-off of Conners teacher form were evaluated clinically for a diagnosis of ADHD, and after clinical evaluations they were asked to participate the study if they met the eligibility criteria. If they accept to participate the study, informed consents were given to cases and parents, and meanwhile, Turkish version of Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version (K-SADS-PL) was also applied to cases. A 5-ml serum was spared from the blood samples that obtained for routine test during diagnosis. Control group was planned to be formed from the blood samples of 60 healthy children that admitted to child psychiatry clinic for counselling. At the time of analyses, diluted according to the directions of manufacturers, incubated with fluorescent staining including antibodies (Anti-Hu, Anti-Yo, and Anti-Ri), and evaluated under immunofluorescent microscope by three specialists. RESULTS: Sixty healthy volunteers and 60 cases with ADHD were included in the study. Some of the samples were excluded from the study due to the damage to laboratory tubes during transport. Assessments were conducted with 52 ADHD and 52 healthy control samples. The male/female ratio was 41/11(78.8%/21.2%) in the patient group and 35/17 (67.3%/32.7%) in the control group ( p  = 0.185). Average age was 9.81 ± 2.41 in the patient group and 9.46 ± 2.14 in the control group ( p  = 0.442). No positive results were obtained for anti-Purkinje antibody in ADHD or control groups. CONCLUSIONS: No evidence regarding the potential role of cerebellar neuroinflammation in the etiology of ADHD was determined in this study. But these results need replication in larger samples and different methods.